Convergent evolution of plant specialized 1,4-naphthoquinones: metabolism, trafficking, and resistance to their allelopathic effects - Meyer, George W; Bahamon Naranjo, Maria A; Widhalm, Joshua R (Journal of experimental botany, 2021)
We highlight how recent discoveries have revealed insight into the evolution of plant specialized 1,4-naphthoquinone metabolism and trafficking, and offer a perspective for investigating mechanisms plants use to tolerate allelopathic 1,4-naphthoquinones. Abstract Plant 1,4-naphthoquinones encompass a class of specialized metabolites known to mediate numerous plant–biotic interactions. This class of compounds also presents a remarkable case of convergent evolution. The 1,4-naphthoquinones are synthesized by species belonging to nearly 20 disparate orders spread throughout vascular plants, and their production occurs via one of four known biochemically distinct pathways. Recent developments from large-scale biology and genetic studies corroborate the existence of multiple pathways to synthesize plant 1,4-naphthoquinones and indicate that extraordinary events of metabolic innovation and links to respiratory and photosynthetic quinone metabolism probably contributed to their independent evolution. Moreover, because many 1,4-naphthoquinones are excreted into the rhizosphere and they are highly reactive in biological systems, plants that synthesize these compounds also needed to independently evolve strategies to deploy them and to resist their effects. In this review, we highlight new progress made in understanding specialized 1,4-naphthoquinone biosynthesis and trafficking with a focus on how these discoveries have shed light on the convergent evolution and diversification of this class of compounds in plants. We also discuss how emerging themes in metabolism-based herbicide resistance may provide clues to mechanisms plants employ to tolerate allelopathic 1,4-naphthoquinones.